The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/198068
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Asthma: Physiological Perspective

Abstract: Obesity induces some pertinent physiological changes which are conducive to either development of asthma or cause of poorly controlled asthma state. Obesity related mechanical stress forces induced by abdominal and thoracic fat generate stiffening of the lungs and diaphragmatic movements to result in reduction of resting lung volumes such as functional residual capacity (FRC). Reduced FRC is primarily an outcome of decreased expiratory reserve volume, which pushes the tidal breathing more towards smaller high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 148 publications
(173 reference statements)
0
15
0
6
Order By: Relevance
“…307 However, abdominal obesity is also associated with an increased prevalence of asthma. 308 It has been reported that both asthma and obesity were independently and synergistically associated with systemic inflammation. 309 Adipokines and asthma.…”
Section: -231mentioning
confidence: 99%
“…307 However, abdominal obesity is also associated with an increased prevalence of asthma. 308 It has been reported that both asthma and obesity were independently and synergistically associated with systemic inflammation. 309 Adipokines and asthma.…”
Section: -231mentioning
confidence: 99%
“…Restrictive type of lung function abnormalities are frequently observed among obese subjects responsible for alteration in respiratory mechanics [60]. Abdominal and thoracic fat deposition are associated with work of breathing [60,61]. Our results indicate a significant decline in the predicted values of both FEV 1 and PEFR with increasing body fat%.…”
Section: Discussionmentioning
confidence: 53%
“…Cirillo et al [21], in an analysis of 18,162 participants from the third National Health and Nutritional Examination Survey, found that total cholesterol and LDL had no significant influence on the decline of FEV 1 , which was also observed in our study. It is important to remember that a decline in FEV 1 may not be a reliable and sensitive measure of airway dysfunction in obesity or related diseases because these structural changes are more dominant in the peripheral/ small airways, and FEV1 is not sensitive enough to evaluate the complexity of these heterogeneous alterations accurately [22]. Thus, the airway resistance could be a more relevant marker to track the infinitesimal change.…”
Section: Discussionmentioning
confidence: 99%